The Systematic Model (ESFE) for Implementation of Open Innovation in Yuchai Group in the Peopleos Republic of China (Global Journal of Human-Social Science, 2019)
Purpose This paper aims to develop a systematic model of open innovation from a systematic view based on the case study of Yuchai Group s practices to illustrate the knowledge input and output in the open-innovation model Design methodology approach The systematic model of open innovation is constructed based on Yuchai Group s practices in the People s Republic of China from a grounded theory approach Findings The results show that from the systematic view the dynamic process of open innovation is divided into four interconnected parts elements integration evaluation of performance and adjustment to the environment For Yuchai Group the element acquisition are much more vital than the development of ideas
Keywords: systematic model; open innovation; organizational change; chinese experience of change